2308. The Prevalence of Antiseptic Tolerance Genes Among Gram-Positive Bloodstream Pathogens in Children. (26th November 2018) - Sommer, Lauren; Krauss, Jennifer; Hulten, Kristina G; Dunn, James; Kaplan, Sheldon L; McNeil, J Chase
Abstract: Background: The presence of the smr and qacA/B genes in Staphylococcus aureus have been correlated with reduced susceptibility to antiseptics. Recently, S. aureus bearing these genes have been reported to be associated with nosocomial acquisition of infection and underlying medical conditions. Antiseptic tolerance (AT) genes have also been reported in coagulase negative staphylococci (CoNS) and enterococci; however, little data are available regarding their prevalence. We sought to describe the frequency of smr and qacA/B among bloodstream isolates of S. aureus, CoNS and enterococci obtained at Texas Children's Hospital (TCH). Methods: Banked CoNS, S. aureus and enterococci isolated from blood cultures collected from October 1, 2016 to October 1, 2017 were obtained from the TCH clinical microbiology laboratory. All isolates underwent PCR for the qacA/B and smr genes. CoNS and enterococci were identified to the species level with MALDI-TOF mass spectrometry. Medical records were reviewed for all cases; CoNS were considered true pathogens if >1 blood culture was positive. Results: 268 CoNS, 19 Enterococcus spp. and 116 S. aureus isolates were identified and included (Figure 1). 83.2% of CoNS possessed at least one AT gene compared with 36.2% of S. aureus and 31.5% of enterococci ( P < 0.001, Figure 2). Neither antiseptic gene was detected in E. faecium isolates ( n = 4) compared with 43.8% of E. faecalis ( P = 0.2). Among CoNS, methicillin-resistance was found more commonly among qacA/B -positive (77.2% vs. 40%, P = 0.04) and smr -positive isolates (93.8% vs. 60.5%, P = 0.02). 38.4% of CoNS bloodstream isolates were considered true infections; among these, the presence of either AT gene was strongly associated with nosocomial infection ( P < 0.001). AT genes in S. aureus were associated with nosocomial infection ( P = 0.007) as well as the diagnosis of CLA-BSI ( P = 0.001). There was no correlation with genotypic AT in enterococci and any examined clinical variable. Conclusion: AT is common among bloodstream staphylococci and E. faecalis isolates at TCH. Among CoNS, the presence of AT genes is strongly correlated with nosocomial acquisition of infection consistent with previous studies in S. aureus . These data suggest that the healthcare environment contributes to AT among staphylococci. Disclosures: All authors: No reported disclosures.